The Relationship Between Effort-Reward Imbalance and Subjective Wellbeing (A Study of Temporary Teachers at Public Junior High Schools in Subdistrict X, West Bandung Regency) - Ulfah Trijayanti; Titania Farah Salsabila (Journal Research of Social Science, Economics, and Management, 2026)
Temporary teachers play an essential role in maintaining the continuity of education, particularly in public junior high schools where teacher availability and student developmental needs require strong professional commitment. However, temporary teachers often face unequal working conditions, including high workloads, administrative responsibilities, additional school duties, limited financial compensation, and uncertain employment status. This study aims to examine the relationship between effort-reward imbalance and subjective well-being among temporary teachers at public junior high schools in Subdistrict X, West Bandung Regency. A quantitative approach with a non-experimental correlational design was employed. The study population consisted of 32 temporary teachers from four public junior high schools, selected using saturated sampling. Data were collected through online questionnaires via Google Forms and analyzed using JASP software, with validity, reliability, normality, descriptive, cross-tabulation, and Pearson Product Moment correlation tests applied. The findings show a significant negative relationship between effort-reward imbalance and subjective well-being, with a correlation coefficient of r = ?0.639 and p < 0.001, indicating that a higher perceived imbalance between effort and reward is associated with lower subjective well-being. Most respondents were categorized as having rewards greater than effort and moderate subjective well-being. The study concludes that fair rewards, social support, professional recognition, and career certainty are important factors in maintaining the psychological well-being of temporary teachers.